Bioethical aspects involved in vaccine testing against SARS-COV-2 virus (Research, Society and Development, 2020)
Objective: to analyze scientific productions that disagree about the relationship between bioethics and vaccine tests' performance against the SARS-CoV-2 virus. Methodology: This is an integrative review, where a bibliographic survey was carried out in the MEDLINE, SCIELO, and VHL databases, using two descriptors "bioethics", "COVID" and "vaccine" associated through the Boolean operator "AND". The analysis of two data was performed descriptively from the comprehensive reading of two articles, categorization, sitting, extraction, and interpretation of two data. Result: the research showed that the population used for our studies was: 68.2% of challenge studies with human beings (HCS), 9.1% of research with the general population and 22.7% of studies with specific populations (pregnant women, blacks, incarcerated population and children), Conclusion: not considered and notorious in the absence of consensus among the studies analyzed, two more studies argue in favor of carrying out two challenge studies, others are exhaustive in stating that the tests without bioethical protection .